2014
DOI: 10.2151/sola.2014-005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regional Difference in Altitude Dependence of Snow Depth Using High Resolve Numerical Experiments

Abstract: This study focuses on the main factor of regional difference in Altitudinal Dependency of Snow Depth (ADSD) and discusses the applicable range of snow cover estimation method with ADSD. We use the high-density surface observational data and a regional climate model in Niigata Prefecture. The estimation method with ADSD produces significant estimation error if the method is applied to broad areas. The high-density observational data show the regional difference of ADSD between windward and leeward areas with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In heavy snow-cover years, winter precipitation clearly increases with elevation ( Fig. 8a), which is consistent with the findings of previous studies (e.g., Uno et al 2014;Asaoka and Kominami 2013). Winter precipitation will increase with the progress of global warming at all elevations.…”
Section: Changes In Daily Snowfall Intensitysupporting
confidence: 91%
“…In heavy snow-cover years, winter precipitation clearly increases with elevation ( Fig. 8a), which is consistent with the findings of previous studies (e.g., Uno et al 2014;Asaoka and Kominami 2013). Winter precipitation will increase with the progress of global warming at all elevations.…”
Section: Changes In Daily Snowfall Intensitysupporting
confidence: 91%
“…We have additionally speculated that the major difference in the simulated precipitation between EXP1 and EXP2 is critically dependent on how topography was resolved. A recent regional modelling study by Uno et al (2014) found that topography (i.e., altitude) effect was critical in simulating the precipitation (i.e., snow) distributions in a nearby region of Toyama prefecture in Japan, further supporting our speculation of the role of orographic forcing in governing the precipitation in Toyama. Chao (2012), on the other hand, points out that GCMs typically simulate excessive precipitation in the vicinity of steep terrain, which would be exacerbated in our higher resolution simulations, and A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT Yasunari et al (2015), Atmospheric Research.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…Certain improvements in some aspects have been observed when the horizontal grid spacing is increased from about ten to several kilometers (e.g., Done et al 2004;Kain et al 2006;Weisman et al 2008;Duc et al 2013;Yashiro et al 2016). NWPs with even finer horizontal grid spacing (~1 km) are now often used for various research purposes including regional climatology (e.g., Uno et al 2014). Forecasts of fog in real cases have been shown to benefit from the finer horizontal grid spacing (333 m) (Boutle et al 2016).…”
Section: Introductionmentioning
confidence: 99%